MENGANALISIS KESALAHAN SISWA KELAS X IPS SMA SWASTA IMELDA DALAM MENYELESAIKAN SOAL FUNGSI PERMINTAAN PADA PEMBELAJARAN EKONOMI - Tria Dita Utami; Umi Kalsum; Suci Frisnoiry; Tiara Fatima Tuzzahra (Lembaga Riset dan Inovasi Kreyat Center, 2023)
This article discusses the results of research on the application of sub-functions in economic mathematics to the demand and supply functions. The demand and supply functions are one of the basics of economics which is simplified into a mathematical economic model by selecting two economic variables, namely the variable price and the variable quantity of goods demanded by consumers or offered by producers. The method used in this study is a qualitative research method with research subjects being class X IPS students of Imelda Private High School. this research aims to find out the mistakes of class X IPS students in working on questions of the demand function, supply function and market equilibrium. The market is said to be balanced if: The number of goods demanded in the market is equal to the number of goods supplied. The price of goods offered by sellers (producers) is equal to the price demanded by buyers (consumers).